Role of Power Converters in Inductive Power Transfer System for Public TransportâA Comprehensive Review - Varikkottil, S. (MDPI, 2022)
IPT (inductive power transfer) charging is a highly flexible concept that allows for charging at any possible opportunity and is highly versatile for vehicles of all sizes. IPT wireless charging technology employs high-power inductive energy transfer between the components embedded into streets and the receiving equipment mounted below the vehicle. When the vehicle moves over the charging point, the contactless charging process is initiated between the components and the vehicle. In this work, the role of power converter topologies in IPT systems are studied for electric vehicle (EV) charging applications. Further, the predominant topologies are compared and analyzed in detail. The contingency in misalignment, loading and frequency shift are discussed for various converter topologies. The tolerance in misalignment poses serious challenges for wireless chargers in EVs. Therefore, there is currently a need to design a symmetric IPT system with multiple decoupled receiving coils. The significance of power inverter topologies for achieving resonance, as well as the generation of high-frequency supply, has been studied in detail. Experimental waveforms that are related to the explanations in this work are provided to substantiate the advantages regarding the converters. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.